Improving Public Health and Governance in COVID-19 Response: A Strategic Public Procurement Perspective - Yan, Ran; Cao, Fuguo (Frontiers in Public Health, 2022)
Good governance is the basis of dealing with major emergencies and protecting public health. It has become a major issue of the central government to construct a scientific procurement and supply system of emergency supplies. This paper constructs the analytical framework of strategic procurement and expounds the realization mechanism of strategic procurement under emergency situation to reflect China’s procurement practice in COVID-19 response, improve public health and governance. By using the methods of case study, semi-structured interviews, and Nvivo text analysis, this study found that emphasizing the strategic function of securing public health, top status of MSG, cross-sector procurement team, strong procurement and supply integration, comprehensive and in-depth procurement synergy mechanism are the successful experiences of China's emergency procurement. However, due to the temporary nature of the emergency procurement mechanism, strategic procurement planning, procurement management specialization and procurement supply integration still need to be improved. Study findings further suggests that in order to improve public health and governance, it is pivotal to reconstruct government procurement law to make it compatible with emergency procurement and transform the government procurement system into strategic procurement in a consistent and coherent way.